Positron Emission Tomography Imaging of Atherosclerosis - Orbay, Hakan (Ivyspring International Publisher, 2013)
Atherosclerosis-related cardiovascular events are the leading causes of death in the industrialized world. Atherosclerosis develops insidiously and the initial manifestation is usually sudden cardiac death, stroke, or myocardial infarction. Molecular imaging is a valuable tool to identify the disease at an early stage before fatal manifestations occur. Among the various molecular imaging techniques, this review mainly focuses on positron emission tomography (PET) imaging of atherosclerosis. The targets and pathways that have been investigated to date for PET imaging of atherosclerosis include: glycolysis, cell membrane metabolism (phosphatidylcholine synthesis), integrin α(v)β(3,) low density lipoprotein (LDL) receptors (LDLr), natriuretic peptide clearance receptors (NPCRs), fatty acid synthesis, vascular cell adhesion molecule-1 (VCAM-1), macrophages, platelets, etc. Many PET tracers have been investigated clinically for imaging of atherosclerosis. Early diagnosis of atherosclerotic lesions by PET imaging can help to prevent the premature death caused by atherosclerosis, and smooth translation of promising PET tracers into the clinic is critical to the benefit of patients.